The Impact of Image on the Retention of Business at the Holland Bakery Citra Raya - Meli Amelina (UMSU, 2023)
Brands are widely recognised as a company's most valuable asset to consumers, which is why brands are important to consumers in their search for product differentiation and uniqueness, as well as in their decision making when choosing products and in increasing consumer confidence in those products. In this study there was a population of 114 respondents, but the researcher took a sample of 100 respondents. The results of this study explain and show that Holland Bakery has created a good brand image among the general public. Based on the results of the calculated and processed questionnaire, consumers choose Holland Bakery as their first choice when buying food products such as the products offered by Holland Bakery, especially bread.